Forty Years After Warnock: Special Needs Education and the Inclusion Process in Denmark. Conceptual and Practical Challenges - Egelund, Niels; Dyssegaard, Camilla Brørup (Frontiers in Education, 2019)
The 1978 Warnock report enshrined the policy of inclusion and changed the way we talk about disability starting in the UK and following became a worldwide trend especially after the Salamanca Statement in 1994. The report thus had a groundbreaking effect on how children with special educational needs should be educated. This article is a tribute to the Warnock report and takes the reader to Denmark to see how special education, inclusion and differentiated instruction in comprehensive schools have been on the agenda in Denmark. Several schools and municipalities have tried to use resources on special education to promote inclusion and differentiation, but rules and regulations and clear incentives for exclusion have hindered this. Only after changing the concept of special education and the introduction of incentives for inclusion in Denmark, the trend has been radically changed. However, there are clear signs that teachers have not yet adapted to the idea of inclusion and are in need of specialist services and resources.